Master Class with Joyce DiDonato at Carnegie Hall (III/III) 2019 Resnick Education Wing - Rossini, Gioacchino 1792-1868; Bellini, Vincenzo 1801-1835; Mozart, Wolfgang Amadeus 1756-1791; Handel, George Frideric 1685-1759 (Carnegie Hall, 2019)
Generous, effervescent, and witty, opera superstar Joyce DiDonato returns to Carnegie Hall for exceptional master classes in which she shares her performing experience and extensive knowledge of the opera repertoire with talented young artists. It is a rare glimpse behind her vocal mastery that is sure to shed light on her motto: "Don't sing it, feel it." Joyce DiDonato appears courtesy of Warner Classics. Photo : © Chris Lee
Keywords: Songs with piano; Singing; Operas; Singing -- Instruction and study; Operas -- Excerpts, Arranged; masterclass; Songs; Instructional and educational works; Filmed performances; Dramatic music; Chamber music; Internet videos